(untitled) (International Journal of Built Environment and Sustainability, 2019)
Traditional teaching practices are often questioned over their failure to generate interest and profound understanding of structures among students that further affect its integration in design solutions. Alternative teaching practices though claim to be more effective, need a sound evaluation measured through assessment of the level of integration of structures in design solutions- the ultimate objective of such courses. This paper evaluates the integration of structures in design solutions of architecture students. The integration assessment framework used for evaluation is based on building systems approach across three dimensions of performance, physicality and visual. It has been developed after comparing four prior frameworks with a 4-point scale and customized to suit the context of the academic environment. The framework offers flexibility in its use for different technical knowledge levels for each successive year of Bachelor of architecture program. The expert opinion followed by testing on design samples from all the program years further refined the framework. The study was then scaled up to include students from first to fourth years for three architecture schools that have completely different institutional environment. The findings revealed that including structural resolution in a design studio mandate may result in higher resolution of structures in design solutions but it is the building typology and student interest that may result in higher visual integration of structures in design solutions. Furthermore, the institutional environment effects can be seen in the setting of studio mandates where architecture school in technical campus laid more emphasis on resolutions of structures and services when compared to other architecture schools